ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PENURUNAN DISIPLINKERJA PEGAWAI KELOMPOK HUKUM ORGANISASI DAN KEPEGAWAIANPADA BADAN PENYULUHAN DAN PENGEMBANGAN SUMBER DAYAMANUSIA PERTANIAN (BPPSDMP) KEMENTRIAN PERTANIAN RI DI JAKARTA - Ardiansyah Saputra, (2021)
ABSTRACT Work discipline is an important thing to pay attention to. Work discipline will be easily seen in employees who have a high sense of responsibility. This research is a qualitative research that aims to describe the work discipline of employees at the Agricultural Extension and Human Resources Development Agency (BPPSDMP) of the Indonesian Ministry of Agriculture in Jakarta. Data collection in this research was carried out by interview, observation and documentation methods. Interviews were conducted in a semi-structured manner with six participants, including one coordinator of the legal group organizational and the staffing group, two sub-coordinators, two staff from each legal group organizational and the staffing group also one subcoordinator of State Property that receiving services from the legal group organizational and the staffing group. To prove the validity of the data in the research, the researcher used the data triangulation method. Furthermore, the data is analyzed by performing data reduction, data presentation and drawing conclusions. The results of the research found two main factors that influence the decrease in employee discipline. definite rules that can be used as guidance and supervision of leaders in the workplace. Remote work during the covid19 pandemic has also changed work styles from before, as the cause of the decrease in employee work discipline in the legal group organizational and the staffing group at the agricultural extension and human resource development agency (BPPSDMP) of the Indonesian Ministry of Agriculture in Jakarta. Keywords: Work Discipline , Employee, Legal Group Organizations And Staffing Group.